Flow and magnetic field properties in the trailing sunspots of active region NOAA 12396. Issue 10 (November 2016) - Verma, M.; Denker, C.; Böhm, F.; Balthasar, H.; Fischer, C. E.; Kuckein, C.; Bello González, N.; Berkefeld, T.; Collados, M.; Diercke, A.; Feller, A.; González Manrique, S. J.; et al.
Abstract: Improved measurements of the photospheric and chromospheric three‐dimensional magnetic and flow fields are crucial for a precise determination of the origin and evolution of active regions. We present an illustrative sample of multiinstrument data acquired during a two‐week coordinated observing campaign in August 2015 involving, among others, the GREGOR solar telescope (imaging and near‐infrared spectroscopy) and the space missions Solar Dynamics Observatory (SDO) and Interface Region Imaging Spectrograph (IRIS). The observations focused on the trailing part of active region NOAA 12396 with complex polarity inversion lines and strong intrusions of opposite polarity flux. The GREGOR Infrared Spectrograph (GRIS) provided Stokes IQUV spectral profiles in the photospheric SiI λ 1082.7 nm line, the chromospheric HeI λ 1083.0 nm triplet, and the photospheric CaI λ 1083.9 nm line. Carefully calibrated GRIS scans of the active region provided maps of Doppler velocity and magnetic field at different atmospheric heights. We compare quick‐look maps with those obtained with the "Stokes Inversions based on Response functions" (SIR) code, which furnishes deeper insight into the magnetic properties of the region. We find supporting evidence that newly emerging flux and intruding opposite polarity flux are hampering the formation of penumbrae, i.e., a penumbra fully surrounding a sunspot is only expected after cessation of flux emergence in proximity to the sunspots. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)